Implementation of Electre Method in Determining Tourism Places in North Sumatera - Triase, Triase; Aprilia, Rima; Khairuna, Khairuna (ZERO: Jurnal Sains, Matematika dan Terapan, 2019)
A tourist in determining the purpose of his tour, must be based on several criteria that are used as a determining factor in choosing. These criteria are taken into consideration by tourists in determining which tourist attractions will be chosen. Thus this study aims to assist tourists in choosing tourist attractions in North Sumatra based on the desired criteria and / or provide information to tourists about the best tourist attractions in North Sumatra in accordance with the desired criteria. The Elimination Et Choix Traduisant La Realita (ELECTRE) method which is a system that uses a multicriter decision making method based on the outranking concept by using a pairwise comparison of alternatives based on each appropriate criterion. This research resulted in a recommendation for natural tourist attractions in North Sumatra, namely Teluk Dalam tourism in the Nias Islands.